Granulomatosis with Polyangiitis (Wegener's Granulomatosis): Evolving Concepts in Treatment - Lynch, Joseph P., III; Derhovanessian, Ariis; Tazelaar, Henry; Belperio, John A. (Seminars in Respiratory and Critical Care Medicine, 2018)
Granulomatosis with polyangiitis (GPA), formerly termed Wegener's granulomatosis, is the most common of the pulmonary vasculitides. GPA typically involves the upper respiratory tract, lower respiratory tract (bronchi and lung), and kidney, with varying degrees of disseminated vasculitis. Cardinal histologic features include a necrotizing vasculitis involving small vessels, extensive “geographic” necrosis, and granulomatous inflammation. The spectrum and severity of the disease is heterogeneous, ranging from indolent disease involving only one site to fulminant, multiorgan vasculitis. Circulating antibodies against cytoplasmic components of neutrophils (ANCAs) play a role in the pathogenesis, and often correlate with activity of the disease. Treatment strategies are evolving. Cyclophosphamide (CYC) plus corticosteroids was the mainstay of therapy for generalized, multisystemic GPA since the 1970s. However, within the past decade, rituximab (RTX), a monoclonal antibody directed against B cells, has been shown to be at least as effective (and possibly more effective) as CYC. Furthermore, the use of RTX may reduce the need for maintenance immunosuppression. Optimal therapy for GPA remains controversial, and additional studies are required to determine the role and duration of maintenance therapy following successful induction therapy.
Keywords: granulomatosis with polyangiitis; Wegener's granulomatosis; granulomatous vasculitis; pulmonary vasculitis; capillaritis; antineutrophil cytoplasmic antibodies; rituximab